2021
DOI: 10.1093/qjmed/hcab230
|View full text |Cite
|
Sign up to set email alerts
|

Auricular acupressure for treating early stage of knee osteoarthritis: a randomized, sham-controlled prospective study

Abstract: Objective We examined whether auricular acupressure (AA) at four specificially preselected AA points can alleviate knee pain and decrease non-steroidal anti-inflammatory drugs (NSAIDs) consumption and its adverse effects for osteoarthritis patients. Methods 62 patients (more than 40 years) with knee osteoarthritis of Kellgren–Lawrence grades of I or II upon radiographic classification were enrolled in this randomized, sham-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These two acupoints play key roles in inhibiting the inflammatory response of the knee joint, improving intraosseous circulation, and reducing knee joint pain. Additionally, Zhang et al [ 33 ] demonstrated that auricular acupressure on the acupoints, such as the knee joint and subcortex, plays a part in relieving analgesia and effectively decreasing NSAID requirements without inducing adverse effects when treating KOA.…”
Section: Discussionmentioning
confidence: 99%
“…These two acupoints play key roles in inhibiting the inflammatory response of the knee joint, improving intraosseous circulation, and reducing knee joint pain. Additionally, Zhang et al [ 33 ] demonstrated that auricular acupressure on the acupoints, such as the knee joint and subcortex, plays a part in relieving analgesia and effectively decreasing NSAID requirements without inducing adverse effects when treating KOA.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine conducted a randomized, sham-controlled prospective study and found that auricular acupressure was analgesic and did not cause any adverse events in the treatment of KOA, and was effective in reducing the use of NSAIDs. A Systematic Review and Meta-Analysis conducted by Wu et al found that patients treated with transcutaneous electric acupoint stimulation (TEAS) were less dependent on opioid analgesics after surgery compared to controls [57]. A large retrospective cohort study by Timothy et al found that acupuncture shows significant advantages in complete opioid discontinuation compared with NSAIDs.…”
Section: Acupuncture Vs Analgesic Drugsmentioning
confidence: 99%
“…Proper management of early-stage KOA13 14 could arrest the disease process, restore joint homeostasis, and thereby reduce the burden of disease 11. Early-stage KOA is a type of KOA that is symptom-focused for diagnosis 11 15.…”
Section: Introductionmentioning
confidence: 99%
“…9 10 Early-stage KOA, as a possible Window of Opportunity to prevent the disease process and improve the quality of life, should be given enough attention. 11 12 Proper management of early-stage KOA 13 14 could arrest the disease process, restore joint homeostasis, and thereby reduce the burden of disease. 11 Early-stage KOA is a type of KOA that is symptom-focused for diagnosis.…”
Section: Introductionmentioning
confidence: 99%